Passive acoustic monitoring of baleen whales in Geographe Bay, Western Australia - Salgado Kent, Chandra; Gavrilov, Alexander; Recalde-Salas, A.; Burton, C.; McCauley, R.; Marley, S. (Acoustical Society of Australia, 2012)
Baleen whales were monitored in Geographe Bay, Western Australia between 2008 and 2011 using passive acoustics. We aimed to monitor migratory timing through Geographe Bay, characterise whale vocalizations, and estimate detection ranges of vocalising whales in different background noise conditions. The results indicated that humpback and blue whales migrated through Geographe Bay every year, however the frequency and timing of their vocalisations varied among years. Humpback whale songs changed in composition among years, but most energy was consistently between 200-500 Hz. Blue whale calls were those of the eastern Indian Ocean pygmy blue whale with low quasi-tonal sounds with harmonics ranging from 20-100 Hz and variable down-sweep impulses with frequencies decreasing from ~100 Hz to ~20 Hz. No significant changes in calls were observed among years. Based on a range independent propagation model, the detection range for vocalising pygmy blue whales was estimated to be between 6-8 km, and for humpback whales ~20-30 km. The prevalence of high levels of noise from vessel traffic affected the detection range significantly for passive acoustic monitoring, and would have also affected the capacity for whales to communicate and perceive important cues in their environment.